2020
DOI: 10.1186/s13063-020-04811-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for diabetic peripheral neuropathy: study protocol for a randomized, placebo-controlled trial

Abstract: Background Diabetic peripheral neuropathy (DPN) is the most common chronic complication of diabetes mellitus that has a considerable impact on quality of life, but there are few effective therapeutic strategies. The aim of this trial is to determine the efficacy and safety of manual acupuncture (MA) versus sham acupuncture (SA) for DPN. Methods/design This is a study protocol for a randomized, placebo-controlled clinical trial. A total of 118 patients with DPN will be recruited and randomly assigned in a 1:1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Os colaboradores Deng, et al (2020) Research, Society and Development, v. 11, n. 15, e346111537330, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i15.37330 8 escalas numéricas de classificação de pontos (NRS). Já o segundo grupo é definido por cuidados de rotina ao qual se trata dos cuidados farmacológicos utilizando as mesmas drogas do primeiro grupo, o qual não receberão tratamento com a acupuntura no período de 16 semanas após a randomização.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Os colaboradores Deng, et al (2020) Research, Society and Development, v. 11, n. 15, e346111537330, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i15.37330 8 escalas numéricas de classificação de pontos (NRS). Já o segundo grupo é definido por cuidados de rotina ao qual se trata dos cuidados farmacológicos utilizando as mesmas drogas do primeiro grupo, o qual não receberão tratamento com a acupuntura no período de 16 semanas após a randomização.…”
Section: Resultsunclassified
“…Todos os pacientes tinham que adivinhar o tipo de tratamento que receberam. Porém neste estudo não tiveram os resultados divulgados(Deng, et al, 2020).Outro estudo foi realizado porHamme, et al (2020), um ensaio clínico randomizado controlado por placebo duplo cego para avaliar o efeito da acupuntura com agulha, acupuntura a laser e a acupuntura a laser por placebo (técnica na qual ocorre a introdução da agulha sem radiação). Foram selecionados 180 participantes, porém 172 completaram o estudo.…”
unclassified
“…Acupuncture, as a traditional treatment method, is based on traditional Chinese medicine (TCM) theory. Studies have shown that acupuncture can signifcantly improve blood glucose and dyslipidemia levels in patients with glucose and lipid metabolism disorders, promote insulin secretion, reduce cholesterol levels, and regulate gene expression in the liver [7][8][9][10][11]. In addition, acupuncture is widely accepted by patients as a safe and efective treatment method.…”
Section: Introductionmentioning
confidence: 99%